Anterior cruciate ligament injury prevention in the young athlete: Evidence-based application - Graziano, J.; Green, D. W.; Cordasco, F. A. (Strength and Conditioning Journal, 2013)
Ab sport participation and early specialization is on the rise, leading to peak performance expectations at a time of major physiological change. Anterior cruciate ligament injuries in the pediatric population were once rare, however, are now seen with greater frequency. Children as young as 10 years of age demonstrate at-risk movement patterns associated with injury. Because late childhood is a critical period for refining movement skills, it is an ideal time to intervene to reduce injury risks. Identification of risk factors, mastery of fundamental skills, and strength training are vital for injury prevention